Generasi Z, Tantangan dan Peluang Bagi Pendidikan - Nisrina Jinan Tuada; Najwa Putri Raihani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Education has a very important role in shaping individuals, especially for Generation Z. There are various challenges and opportunities faced by Generation Z in the realm of education. Although digital tools offer great opportunities in education, such as flexible access to information and interactive learning methods, technology also brings challenges, including mental health problems and disorders due to excessive use of social media. The method used is a qualitative approach with literature studies from various relevant sources. The research results show that although there is a gap between traditional learning methods and Generation Z's digital preferences, the use of technology and social media in education can be an opportunity to create learning that is more flexible, interactive and suited to their needs.